2008
DOI: 10.1159/000129365
|View full text |Cite
|
Sign up to set email alerts
|

Metal Concentrations in Plasma and Cerebrospinal Fluid in Patients with Alzheimer’s Disease

Abstract: Background/Aims: The homeostasis of essential metals such as copper, iron, selenium and zinc may be altered in the brain of subjects with Alzheimer’s disease (AD). Methods: Concentrations of metals (magnesium, calcium, vanadium, manganese, iron, cobalt, nickel, copper, zinc, selenium, rubidium, strontium, molybdenum, cadmium, tin, antimony, cesium, mercury and lead) were determined in plasma and cerebrospinal fluid (CSF) by inductively coupled plasma mass spectrometry in 173 patients with AD and in 87 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 59 publications
8
116
5
1
Order By: Relevance
“…They found that the differences were not statistically significant for all regions, but the highest Mn levels were found in the basal ganglia in both the controls and the AD patients (39). In a previous study, CSF concentrations of V, Mn, Rb, Sb, Cs, and Pb were significantly lower in patients with AD (N = 264; P ≤ 0.007) than in healthy controls (40). In the current study, hair Mn levels were found to be significantly higher in patients with AD than in the control group.…”
Section: Discussionsupporting
confidence: 50%
“…They found that the differences were not statistically significant for all regions, but the highest Mn levels were found in the basal ganglia in both the controls and the AD patients (39). In a previous study, CSF concentrations of V, Mn, Rb, Sb, Cs, and Pb were significantly lower in patients with AD (N = 264; P ≤ 0.007) than in healthy controls (40). In the current study, hair Mn levels were found to be significantly higher in patients with AD than in the control group.…”
Section: Discussionsupporting
confidence: 50%
“…A few studies found correlations between low serum Mg levels and cognitive impairment in other diseases, including Alzheimer's disease (AD) (25,26). Some data seem also to indicate low brain Mg levels in patients with AD, although other studies have found no correlation between Mg and AD (27,28). A more recent longitudinal study in cognitively healthy individuals followed-up for 8 years showed that higher dietary Mg intake was associated with lower risk of mild cognitive impairment (29).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many studies have reported an increase of circulating copper in AD patients with respect to healthy controls (Arnal et al, 2010, Bocca et al, 2005, Gonzalez et al, 1999, Smorgon et al, 2004, Squitti et al, 2006, Squitti et al, 2002a, Squitti, et al, 2003, Zappasodi, et al, 2008, many others no variation (Basun et al, 1991, Baum et al, 2010, Gerhardsson et al, 2008, Jeandel et al, 1989, Kapaki et al, 1989, Molina et al, 1998, Ozcankaya & Delibas, 2002, Snaedal et al, 1998, and two very recent studies even a decrease of copper in plasma (Vural et al, 2010) and serum of AD patients. Moreover, the latter two studies are in line with two older studies showing that low plasma copper concentrations correlate with clinical worsening in AD, one reporting a copper plasma-decrease in more severe vs. less severe patients (Kessler et al, 2006), and the other a direct correlation between low plasma copper concentrations and cognitive decline (Pajonk et al, 2005).…”
Section: Coppermentioning
confidence: 98%